2018
DOI: 10.5935/2595-0118.20180034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic pain in Brazil: a descriptive study

Abstract: BACKGROUND AND OBJECTIVES: Very little is known about the epidemiology of chronic pain in Brazil; especially in the case of multiple pain prevalence surveys. Knowing about the prevalence of chronic pain in the Brazilian population is an important step in revealing the scope and magnitude of its effects, providing a guide to preventive and intervention strategies, mainly public policies. The objective is to review descriptively the publications made in Brazil to estimate the prevalence of chronic pain in the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
27

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 16 publications
3
23
0
27
Order By: Relevance
“…Pain is an extremely prevalent symptom. A review of studies on the prevalence of CP in the Brazilian population found a range from 29.3 to 73.3%, affecting more women than men, and the most prevalent location was the dorsal/lumbar region 26 . The higher prevalence of CP in the elderly Brazilian population is significantly associated with being female, having less education, and worse economic status 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Pain is an extremely prevalent symptom. A review of studies on the prevalence of CP in the Brazilian population found a range from 29.3 to 73.3%, affecting more women than men, and the most prevalent location was the dorsal/lumbar region 26 . The higher prevalence of CP in the elderly Brazilian population is significantly associated with being female, having less education, and worse economic status 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura médica, dor crônica é definida como aquela que tem duração maior que três meses depois da injúria que a causou, ou seis meses para fins de pesquisa, sendo que estudos recentes sobre o tema mostram que grande parte do que foi coletado de informações no Brasil remontam aos últimos 10 anos, com prevalência compreendida de 29,3 a 73,3%, sendo maior em mulheres (Vasconcelos & Araújo, 2018). É importante destacar também que, em nível nacional, temos poucos estudos sobre epidemiologia da dor e a maior parte deles foi conduzida em situações específicas e seletivas, tais como em população de idosos (Dellaroza et al, 2007), população adulta (Kreling, Cruz, & Pimenta, 2006) e grupos de fumantes (Fishbain et al, 2007), além de estudos de uma determinada região do corpo e não considerando o fenômeno da dor crônica como um todo, por exemplo, estudo de dores de cabeça (Queiroz, Barea, & Blank, 2006) e dores muscular-esquelética (Teixeira et al, 2001).…”
Section: Covid-19 E Dor Crônicaunclassified
“…Estima-se que a prevalência de dor crônica no mundo esteja em torno de 7% a 40% da população mundial sofre de dor crônica (Dellaroza, Pimenta, e Matsuo, 2007;Fishbain et al, 2007). No Brasil, embora não haja muitos estudos epidemiológicos, algumas pesquisas confirmam incidência semelhante a essa estimada pela International Association for the Study of Pain (IASP) com uma média de prevalência em torno de 35,5% (Vasconcelos & Araújo, 2018) com grandes variações nos diferentes estados brasileiros.…”
Section: Introductionunclassified
“…Observational studies on chronic pain among older people in Brazil all have a cross-sectional design and only offer data on direct associations. These studies report the prevalence of chronic pain to range from 29.3% to 73.3%, with a greater frequency in the female sex 11,12 .…”
Section: Introductionmentioning
confidence: 99%